Fight or flight: Can marketing tools help consumers cope with self-discrepancies and social identity threat? - Kateryna Ukrainets; Christian Homburg (Journal of Consumer Behaviour, 2021)
Self-discrepancy between the actual and ought self-concept is harmful to individuals, causing them to experience psychological discomfort. Previous consumer research has repeatedly demonstrated that self-discrepancies motivate consumers to cope with their negative psychological consequences. However, despite the potential of marketing tools to influence consumers' affective reactions, consumer research remains silent on how firms can help consumers cope with psychological discomfort caused by self-discrepancies. We apply the “approach–avoidance” coping classification to the firm context and suggest two marketing tools—cause-related marketing (CRM) and a spacious store layout—as moderators of the relationships between experienced self-discrepancy and a threat to a consumer's social identity and between social identity threat and store loyalty/store attitude. In a scenario-based experimental study, we collect data and apply structural equation modeling for data analysis. The results confirm that both suggested marketing tools can effectively mitigate the negative effects of social identity threat on store loyalty and attitude. Furthermore, a spacious store layout exerts a stronger moderating effect than CRM.
Keywords: 320